Changes in lower extremity biomechanics due to a basketball-specific fatigue protocol - Peng, L.; Hanjun, L. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to evaluate the effects of a basketball-specific fatigue protocol on lower extremity biomechanics during a jump-stop task. The subjects consisted of twelve male collegiate basketball athletes free of lower extremity injury. Participants performed six trials of jump-stop task. A basketball-specific fatigue protocol was performed and the biomechanical characteritics of lower extremities were conducted by paired t-tests with the significance level set at 0.05. The specific fatigue protocol caused a reduction of hip abduction and posterior GRF. An increase of approach speed, knee flexion angle and vertical GRF was also shown during post-fatigue condition . There was no difference on other variables caused by fatigue. The basketball-specific fatigue protocol altered lower extremity biomechanics during jump-stop tasks.